Food as Sculpture. - Bottinelli, Silvia.; Herrera, Mary.; Reytblat, Jessica.; McKenzie, Shannon.; Hasanen, Laura.; Mundy, Dael.; Wampold, Charlotte.; Kappel, Quinton.; Vachon, Joslin.; Morris, Natasha.; Sowa, Claire.; Wong Yu Lam, Chloe. (Tufts University. Tisch Library., 2017)
The papers incorporated in this volume are the outcome of a four semester-long process. The authors started working on their essays in the context of [Bottinelli's] Fall 2014 class titled Food as Sculpture, and then continued to research and write during the Spring 2015. In the span of eight months, they gathered information on some theoretical implications and historical embodiments of 'food art'; started to shape interests of their own; identified research topics; found and read multiple sources; and initially wrote several drafts of their texts before submitting a final version.